Desempenho Produtivo de Animais de Quatro Raças Zebuínas, Abatidos em Três Estádios de Maturidade. 2. Características da Carcaça - Jorge, André Mendes [UNESP]; De Alencar Fontes, Carlos Augusto; Paulino, Mário Fonseca; Gomes Jr., Paulo; Ferreira, Juliana Nardelli (My University, 1999)
With the aim to study carcass traits, nine Gyr, nine Guzera, nine Nellore and nine Mocho Tabapuã bulls, averaging, respectively, 357.6, 362.0, 368.6, and 376.4 kg of initial live weight and 24 months of age were used in this study. The animals from each breed were randomly assigned to individual pens and were full fed a diet containing 50% concentrate, dry matter basis, until the slaughter weights (405, 450 and 500 kg LW). At slaughter the empty body weight was determined. There were no differences among breeds or slaughter weights on the traits studied, except for whole alcatra cut yield. For this trait there was a interaction effect between breed and category. The yield decreased in Gyr breed, as slaughter weight increased, but did not change in the other breeds. There were no differences among breeds regarding to any one of the physical composition. Slaughter weight did not influence carcass physical composition and loin eye area, however affected the carcass length and back fat thickness.
Productive Performance of Four Zebu Breed Beef Cattle Slaughtered at Different Stages of Maturity. 2. Carcass Traits
Keywords: Back fat thickness; Beef cattle; Carcass traits; Length; Loin eye area; Physical composition; Zebu